Griffing's Methods Comparison for General and Specific Combining Ability in Cucumber - J. A. Olfati; H. Samizadeh; B. Rabiei; Gh. Peyvast (The Scientific World Journal)
A comparison among two forms of half-diallel analysis was made. The different half-diallel techniques used were Griffing's model I, method 2 and 4. These methods of diallel analysis were found to be interrelated. However, as Griffing's model I, method 4 partitioned heterosis into different components as well as gave information about combining ability and this method had certainly some advantages over the other. The results further indicated using parental generations in the second Griffing method may cause biased estimate of the GCA and SCA variances. Thus, using the fourth Griffing method is more suitable than the other methods in providing time, cost, and facilities, and it is recommended as an applicable method.